Prognosis of Patients With Familial Hypercholesterolemia After Acute Coronary Syndromes. Issue 10 (6th September 2016) - Nanchen, David; Gencer, Baris; Muller, Olivier; Auer, Reto; Aghlmandi, Soheila; Heg, Dik; Klingenberg, Roland; Räber, Lorenz; Carballo, David; Carballo, Sebastian; Matter, Christian M.; Lüscher, Thomas F.; et al.
Abstract : BACKGROUND: Patients with heterozygous familial hypercholesterolemia (FH) and coronary heart disease have high mortality rates. However, in an era of high-dose statin prescription after acute coronary syndrome (ACS), the risk of recurrent coronary and cardiovascular events associated with FH might be mitigated. We compared coronary event rates between patients with and without FH after ACS. METHODS: We studied 4534 patients with ACS enrolled in a multicenter, prospective cohort study in Switzerland between 2009 and 2013 who were individually screened for FH on the basis of clinical criteria according to 3 definitions: the American Heart Association definition, the Simon Broome definition, and the Dutch Lipid Clinic definition. We used Cox proportional models to assess the 1-year risk of first recurrent coronary events defined as coronary death or myocardial infarction and adjusted for age, sex, body mass index, smoking, hypertension, diabetes mellitus, existing cardiovascular disease, high-dose statin at discharge, attendance at cardiac rehabilitation, and the GRACE (Global Registry of Acute Coronary Events) risk score for severity of ACS. RESULTS: At the 1-year follow-up, 153 patients (3.4%) had died, including 104 (2.3%) of fatal myocardial infarction. A further 113 patients (2.5%) experienced nonfatal myocardial infarction. The prevalence of FH was 2.5% with the American Heart Association definition, 5.5% with the Simon Broome definition, and 1.6% with the Dutch Lipid Clinic definition. Compared with patients without FH, the risk of coronary event recurrence after ACS was similar in patients with FH in unadjusted analyses, although patients with FH were >10 years younger. However, after multivariable adjustment including age, the risk was greater in patients with FH than without, with an adjusted hazard ratio of 2.46 (95% confidence interval, 1.07–5.65; P =0.034) for the American Heart Association definition, 2.73 (95% confidence interval, 1.46–5.11; P =0.002) for the Simon Broome definition, and 3.53 (95% confidence interval, 1.26–9.94; P =0.017) for the Dutch Lipid Clinic definition. Depending on which clinical definition of FH was used, between 94.5% and 99.1% of patients with FH were discharged on statins and between 74.0% and 82.3% on high-dose statins. CONCLUSIONS: Patients with FH and ACS have a >2-fold adjusted risk of coronary event recurrence within the first year after discharge than patients without FH despite the widespread use of high-intensity statins. Abstract : Supplemental Digital Content is available in the text.